The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1109/jqe.2014.2364199
|View full text |Cite
|
Sign up to set email alerts
|

Full-Vectorial Finite-Element Analysis of Acoustic Modes in Silica Waveguides

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent V. GrattanAbstract-A finite-element code has been developed to study the vector acoustic modes in high index contrast silica optical waveguides. Detailed spatial variations of the transverse and longitudinal displacement vectors are shown for the bending, radial, and torsional modes. The variation of the frequency shift due to the stimulated Brillouin scattering and the overlaps see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Such waveguides operating in the single-mode regime have a wide range of applications in sensing and also exploit optical nonlinearities. In these high index contrast optical waveguides, where the light is strongly confined in the core, such optical waveguides can also confine both the shear and longitudinal acoustic modes which results in the formation of hybrid modes similar to those reported recently [11,22]. In this section, an analysis of some of the acoustic modes in SiO 2 nanowires, surrounded by noble gases, has been carried out.…”
Section: A Weakly Guiding Silica (Sio 2 ) Fibermentioning
confidence: 63%
See 1 more Smart Citation
“…Such waveguides operating in the single-mode regime have a wide range of applications in sensing and also exploit optical nonlinearities. In these high index contrast optical waveguides, where the light is strongly confined in the core, such optical waveguides can also confine both the shear and longitudinal acoustic modes which results in the formation of hybrid modes similar to those reported recently [11,22]. In this section, an analysis of some of the acoustic modes in SiO 2 nanowires, surrounded by noble gases, has been carried out.…”
Section: A Weakly Guiding Silica (Sio 2 ) Fibermentioning
confidence: 63%
“…In such cases, a rigorous full-vectorial analysis [9,10] is required for the accurate characterization of the acoustic wave propagation in these optical waveguides. In this work, a numerical approach based on the versatile finite element method (FEM) has been developed [11], and it is shown that this can be applied to the analysis of arbitrarily shaped both weakly and strongly guiding acoustic waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…Another common computational approach is the finite element method (FEM). Several groups have used FEM for the design or analysis of the Brillouin scattering spectra in optical fiber [87][88][89][90][91]. One advantage is that these methods may offer greater computational efficiency for more complicated fiber structures, especially with the use of commercial software [91].…”
Section: The Materialsmentioning
confidence: 99%